Literatura w grach wideo. Rozeznanie wstępne - Ołownia, Mikołaj (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
This article is the first attempt to describe the issue of using literary texts in role-playing video games. The author discusses the function of this type of literature, with particular emphasis on its impact on immersion, and presents his own classification of literary texts used in games.